Centrifugal air-assisted melt agglomeration for fast-release "granulet" design : development of a bladeless prototype / Nafisah Musa - Musa, Nafisah (2012)
Conventional melt pelletization and granulation processes produce round and dense, and irregularly shaped but porous agglomerates respectively. This study aimed to design centrifugal air-assisted melt agglomeration technology for manufacture of spherical and yet porous "granulets" for ease of downstream manufacturing and enhancing drug release. A bladeless agglomerator, which utilized shear-free air stream to mass the powder mixture of lactose filler, polyethylene glycol binder and poorly water-soluble tolbutamide drug into "granulets", was developed. The inclination angle and number of vane, air-impermeable surface area of air guide, processing temperature, binder content and molecular weight were investigated with reference to "granulet" size, shape, texture and drug release properties. Unlike fluid-bed melt agglomeration with vertical processing air flow, the air stream in the present technology moved centrifugally to roll the processing mass into spherical but porous "granulets" with a drug release propensity higher than physical powder mixture, unprocessed drug and dense pellets prepared using high shear mixer. The fast-release attribute of "granulets" was ascribed to porous matrix formed with a high level of polyethylene glycol as solubilizer. The agglomeration and drug release outcomes of centrifugal air-assisted technology are unmet by the existing high shear and fluid-bed melt agglomeration techniques.